The prognostic value of Eastern Cooperative Oncology Group performance status on overall survival among patients with metastatic prostate cancer: a systematic review and meta-analysis - Assayag, Jonathan; Kim, Chai; Chu, Haitao; Webster, Jennifer (Frontiers in Oncology, 2023)
Background: There is heterogeneity in the literature regarding the strength of association between Eastern Cooperative Oncology Group performance status (ECOG PS) and mortality. We conducted a systematic review and meta-analysis of studies reporting the prognostic value of ECOG PS on overall survival (OS) in metastatic prostate cancer (mPC). Methods: PubMed was searched from inception to March 21, 2022. A meta-analysis pooling the effect of ECOG PS categories (≥2 vs. <2, 2 vs. <2, and ≥1 vs. <1) on OS was performed separately for studies including patients with metastatic castration-resistant prostate cancer (mCRPC) and metastatic castration-sensitive prostate cancer (mCSPC) using a random-effects model. Analyses were stratified by prior chemotherapy and study type. Results: Overall, 75 studies, comprising 32,298 patients, were included. Most studies (72/75) included patients with mCRPC. Higher ECOG PS was associated with a significant increase in mortality risk, with the highest estimate observed among patients with mCRPC with an ECOG PS of ≥2 versus <2 (hazard ratio [HR]: 2.10, 95% confidence interval [CI]: 1.87–2.37). When stratifying by study type, there was a higher risk estimate of mortality among patients with mCRPC with an ECOG PS of ≥1 versus <1 in real-world data studies (HR: 1.98, 95% CI: 1.72–2.26) compared with clinical trials (HR: 1.32, 95% CI: 1.13–1.54; p < 0.001). There were no significant differences in the HR of OS stratified by previous chemotherapy. Conclusions: ECOG PS was a significant predictor of OS regardless of category, previous chemotherapy, and mPC population. Additional studies are needed to better characterize the effect of ECOG PS on OS in mCSPC.